2005
DOI: 10.1117/12.588474
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon fluorescence microscope with a hollow-core photonic crystal fiber

Abstract: Since the first demonstration in 1990, two-photon fluorescence microscopy (TPFM) has made a great impact on biomedical researches. With its high penetration ability, low out-of-focus photodamage, and intrinsic three-dimensional (3D) sectioning capability, TPFM has been widely applied to various medical diagnosis and genome researches. Recently, single-mode optical fibers were introduced into the TPFM systems for remote optical pulse delivery. Fiberbased TPFM has advantages including isolating the vibration fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…PCF has various potential applications in nonlinear microscopy imaging and telecommunications areas, since it has better optical characteristics than TIR-based optical fibers in terms of guiding, dispersion, and refraction (Lourtioz, 2005). It has been shown that the dispersion of ultrafast optical pulses can be significantly reduced by using photonic crystal fibers (Gobel and others, 2004; Kim and others, 2005; McConnell and Riis, 2004; Tai and others, 2004). Importantly, photonic crystal fibers also offer better performance than traditional fibers in conducting high power ultrafast optical pulses.…”
Section: Introductionmentioning
confidence: 99%
“…PCF has various potential applications in nonlinear microscopy imaging and telecommunications areas, since it has better optical characteristics than TIR-based optical fibers in terms of guiding, dispersion, and refraction (Lourtioz, 2005). It has been shown that the dispersion of ultrafast optical pulses can be significantly reduced by using photonic crystal fibers (Gobel and others, 2004; Kim and others, 2005; McConnell and Riis, 2004; Tai and others, 2004). Importantly, photonic crystal fibers also offer better performance than traditional fibers in conducting high power ultrafast optical pulses.…”
Section: Introductionmentioning
confidence: 99%
“…We observe minimal pulse broadening from 750 to 800 nm with 100 fs pulse width input. However, some prior studies [13][14] indicate that pulse broadening is closely related to GVD and is quite large in the similar range of wavelength for hollow core photonic bandgap crystal fiber but using an input pulse width of 200 fs. Therefore, the pulse propagation equation should be examined in detail in order to explain the discrepancy between these studies.…”
Section: Spectral Distortion and Pulse Broadening Observation As A Fumentioning
confidence: 97%
“…7,8 PCFs can be made with parameters impossible to achieve in standard fibers, which has led some researchers and investigators to suggest that PCFs could become the ultimate transmission waveguide for electromagnetic fields. 9 As long as PCFs fulfill their potentials, they could have important applications in spectroscopy, 10 metrology, 11 biomedicine, 12 imaging, 13 optical coherence tomography (OCT), 14 sensing, [15][16][17][18] and telecommunications. [19][20][21][22][23] On the other hand, although long-period gratings (LPGs) has emerged at the same time as PCFs, 24 the fabrications of PCF-based fiber components have attracted great attention in resent years.…”
Section: Introductionmentioning
confidence: 99%